Physical education and sport in pedagogical concepts - historical context - Kaźmierczak, Arkadiusz (Journal of Education, Health and Sport, 2018)
The postulates of outstanding representatives of pedagogical thought presented since the time of the Hellenic pedagogy on physical education and sport have contributed to the inclusion of their content in the education system, and have become a source of creative inspiration in building the theory and practice of physical education and sporting activity. Remarkable thinkers of their eras; Plato, Aristotle, Plutarch, Saint Thomas Aquinas, J.Locke, J.J.Rousseau, T.Arnold, P.Coubertin, W.F.Froebel, H.Spencer, M.Montessori, C.Freinet and J.Dewey, in an exceptionally mature way emphasized the universal values of physical education and sport in the process of education and training of the young generation.